Implementation of Activating Methods of Teaching Polish as a Foreign Language to Children (Reflections about a Summer Course of Polish in Moldova) - Pokorska, Michalina (Ludicity in (Glotto)Didactic, 2020)
This article regards to author’s didactic experience concerning her teaching children on a Polish course in Moldova. The first part is a presentation of the Polish diaspora in this country. Next it provides a description of the Association “Polski Dom w Bielcach”, whose main goal is to integrate The Polish community in Moldova and give it a permanent contact with the Polish language and culture. The author writes about specificity of teaching children referring to Development Psychology. The major part of the text includes a presentation of the activating methods of teaching implemented by the author on a course of Polish to children in Moldova. She used primarily lively songs and educational games with motor activities. The pupils satisfaction and engagement proved that the applied teaching methods were appropriate and efficient.